TERRITORY, AGROCHEMICALS, AND THE HEALTH-DISEASE PROCESS: STUDY OF THE USE OF PESTICIDES IN AGRICULTURAL PRODUCTION AND ADVERSE EFFECTS ON REPRODUCTIVE HEALTH IN THE RESIDENT POPULATION OF MUNICIPALITIES IN THE NORTHEAST I AND NORTHEAST II HEALTH REGIONS, - Pereira, Augusto José de Oliveira; Tavares, Giovana Galvão (CIPEEX, 2025)
The study analyzed the relationship between the use of pesticides in agricultural production (sugarcane, soybeans, and corn) and adverse effects on the reproductive health of the population residing in the Northeast I and Northeast II health regions of Goiás between 2010 and 2022. The objective was to identify agricultural producing municipalities and cases of reproductive disorders associated with exposure to agrochemicals. The research was exploratory and descriptive, using data from Ministry of Health information systems, such as SINAN. The analysis included information on exogenous intoxications, type of exposure, and case progression. In addition, the prevalence of reproductive disorders, such as infertility, spontaneous abortions, and hormonal changes, was investigated. The results revealed that most poisonings in the regions studied were acute, although chronic cases were also reported. Exposure to agrochemicals was associated with significant reproductive disorders in both men and women, with emphasis on interference with fertility and gestational complications. There was a higher incidence of poisoning due to suicide attempts and habitual use, highlighting the precariousness of pesticide management. The study concludes that there is a need for greater regulation and control of agrochemical use, as well as the implementation of more effective prevention policies to protect the reproductive health of the exposed population.